Experimental studies of some features of beam-plasma discharge initial stage - Butenko, V.I.; Ivanov, B.I.; Prishchepov, V.P. (Вопросы атомной науки и техники, 2005)
In case of gas pressure increasing, the plasma density rapidly increases at p=(1-2)*10⁻⁴ Torr, due to the beam-plasma discharge start (BPD). For fixed pressure above 2*10⁻⁴ Torr, the BPD start depends from the interaction length L and beam current I, with relation I∝ L⁻¹ . Measurements of the electron velocity distribution were performed using an UHF method and a multi-electrode probe. The start conditions are agreed with theoretical estimations. При збільшенні тиску газу до (1-2)*10⁻⁴ Торр щільність плазми різко підвищуется завдяки пучково-плазмовому розряду (ППР). При фіксованому тиску вище 2*10⁻⁴ Торр початок ППР залежить від довжини взаємодії L та струму пучка I: I∝L⁻¹. Були проведені вимірювання розподілу електронів по швидкостям СВЧ методом та багатосітковим зондом. Умови старту ППР узгоджуються із теоретичними оцінками. При увеличении давления газа до (1-2)*10⁻⁴ Торр плотность плазмы резко возрастает благодаря пучково- плазменному разряду (ППР). При фиксированном давлении выше 2*10⁻⁴ Торр начало ППР зависит от длины взаимодействия L и тока пучка I: I∝ L⁻¹. Проведены измерения распределения электронов по скоростям СВЧ методом и многосеточным зондом. Условия старта ППР согласуются с теоретическими оценками.